Semarang City's Resilient Strategy Facing Covid-19 - Adi Ekopriyono (Institut Teknologi Sepuluh Nopember, 2021)
Semarang City is the first city in Indonesia to be selected in the 100 Resilient Cities (100 RC) Program. This position raises the hope that this city has more potential than other cities to prevent and control the spread of Covid-19. The policies pursued through Restrictions on Community Activities and the Candi Hebat Siaga Village Program have not yet been optimal in breaking the chain of Covid-19 spread. This study uses a descriptive qualitative approach, examines the factors that influence, and formulates the steps that need to be taken to increase its effectiveness. The most prominent factor found in this study is the weak resilience of local culture concerning the prevention and control of Covid-19. This weakness causes the community to be less disciplined in implementing health protocols and the apparatus less control over the implementation of policies.